Antimicrobial Silk Fibroin Methacrylated Scaffolds for Regenerative Endodontics - Narayanam, Ramyasaketha; Cardoso, Lais M. [UNESP]; dos Reis-Prado, Alexandre H.; de Carvalho, Ana Beatriz G. [UNESP]; Anselmi, Caroline [UNESP]; Mahmoud, Abdel H.; Fenno, J. Christopher; Dal-Fabbro, Renan; Bottino, Marco C. (Elsevier, 2024)
Introduction: Recognizing the necessity of novel disinfection strategies for improved bacterial control to ultimately favor tissue regeneration, this study developed and characterized antibiotics-laden silk fibroin methacrylated (SilkMA) scaffolds for regenerative endodontics. Methods: SilkMA-based solutions (10% w/v) containing Clindamycin (CLI) or Tinidazole (TIN) (0 – control; 5, 10, or 15% w/w) or the combination of both drugs (BiMix CLI/TIN 10%) were electrospun and photocrosslinked. Morphology and composition were assessed using scanning electron microscopy and Fourier-transform infrared spectroscopy. Additionally, swelling and degradation profiles were also determined. Cytotoxicity was evaluated in stem cells from apical papilla. Antibacterial efficacy was tested using direct and indirect contact assays against Aggregatibacter actinomycetemcomitans/Aa, Actinomyces naeslundii/An, Enterococcus faecalis/Ef, and Fusobacterium nucleatum/Fn. E. faecalis biofilm inhibition on dentin discs was specifically evaluated for BiMix-laden scaffolds. Data were statistically analyzed with a significance level of 5%. Results: Scanning electron microscopy revealed that all scaffolds had similar characteristics, including fiber morphology and bead absence. Fourier-transform infrared spectroscopy showed the incorporation of CLI and TIN into the fibers and in BiMix scaffolds. Antibiotic-laden scaffolds exhibited lower swelling capacity than the control and were degraded entirely after 45 days. Scaffolds laden with CLI, TIN, or BiMix throughout all time points did not reduce stem cells from apical papilla's viability. CLI-laden scaffolds inhibited the growth of Aa, An, and Ef, while TIN-laden scaffolds inhibited Fn growth. BiMix-laden scaffolds significantly inhibited Aa, An, Ef, and Fn in direct contact, and their aliquots inhibited An and Fn through indirect contact, with additional biofilm inhibition against Ef. Conclusions: BiMix-laden SilkMA scaffolds are cytocompatible and exhibit antimicrobial effects against endodontic pathogens, indicating their therapeutic potential as a drug delivery system for regenerative endodontics.
Keywords: Clindamycin; regenerative endodontics; silk; tinidazole; tissue engineering